741 A complex clinical mosaic of severe autoimmune calcific constrictive pericarditis with striking haemodynamic response to immunosuppressive therapy. (8th December 2021) - Bertelli, Michele; Bertolini, Davide; Di Nicola, Federico; Armillotta, Matteo; Sansonetti, Angelo; Foà, Alberto; Angeli, Francesco; Rinaldi, Andrea; Galié, Nazzareno; Pizzi, Carmine
Abstract: Autoimmune constrictive pericarditis constitutes a conundrum to modern cardiology with much uncertainty surrounding both pathophysiology and optimal treatment strategies. We hereby describe the case of a 35-year-old woman of Nigerian origin with severe right heart failure secondary to calcific constrictive pericarditis. Her past medical history included coagulation factor XI deficiency, leukopenia, 2nd trimester miscarriage and premature labour due to placenta previa with fibrin deposition. Further investigations revealed atrial fibrillation, severe biatrial enlargement, moderate tricuspid and mitral regurgitation, pericardial thickening, post-capillary pulmonary hypertension and right ventricular dip-and-plateau pattern, compatible with severe constrictive pericarditis. Extensive screening for infectious and autoimmune causes only revealed borderline positive ANA (1:80). Thereafter, the patient underwent complete surgical pericardiectomy with pericardial biopsies revealing fibrous thickening, diffuse calcification and lymphocyte/macrophage infiltrates, in the absence of giant multinucleated cells or granulomas. The patient was later discharged but soon experienced relapse of exertional dyspnoea presenting with right-sided haemo-pneumothorax (requiring pleural drainage), diffuse alveolar haemorrhage, large right-sided basal and infrascissural pleural effusion, and ascites. She was treated with high dose iv furosemide, oral ibuprofen and colchicine, suspension of rate control medications, achieving initial reduction in pulmonary oedema and ascites, relapsing however after attempts to switch to oral diuretic therapy. Due to the finding of persistent lymphopenia, further immunological tests were conducted, revealing raised IgG1 levels as well as altered peripheral lymphocyte populations (raised CD4+/CD8+ ratio and CD8+ central memory, reduced CD8 effector memory). This finding in conjunction with the history of factor XI deficiency, 2nd trimester miscarriage and placental fibrin deposition as well as the observation of painful cutaneous nodules at sites of venepuncture, suggestive of Koebner's phenomenon, veered the diagnostic focus to a potential autoimmune aetiology and in particular to systemic lupus erythematosus (>10 ACR-EULAR score points with case reports describing all the above as potential disease manifestations). Furthermore, revision of thoracic CT scans, demonstrated bilateral migratory peribronchovascular nodules with ground-glass halo. CT- guided biopsies thereof were performed revealing focal alveolar damage with capillaritis and alveolar haemorrhage, further corroborating the clinical suspicion of autoimmune disease and justifying the introduction of high-dose oral corticosteroid therapy. In liaison with our tertiary rheumatology centre, the patient was later switched to mycophenolate with gradual weaning from corticosteroid. Concurrent cardiological follow-up revealed persistence of good haemodynamic status (NYHA class II, absence of pulmonary oedema and ascites) with oral diuretic therapy, regression of cutaneous symptoms and echocardiography demonstrating consistent reduction in both mitral and tricuspid regurgitation. This constitutes to our knowledge the first report of autoimmune calcific constrictive pericarditis with significant haemodynamic response to immunosuppressive therapy. Despite the relative rarity of this disease entity, early recognition and instatement of immunosuppressive treatment may prove fundamental to halt and potentially reverse the haemodynamic progression of this highly morbid condition.